Tobacco product cessation and prenatal care utilization: A Pregnancy Risk Assessment Monitoring System phase 8 study of conventional cigarette, e-cigarette, and dual-use associated behaviors - Rathika Damodara Shenoy; Michael Weitzman; Juan M. Acuña (PLoS ONE, 2026)
Background Pregnancy is a critical window for tobacco cessation; socio-demographic correlates and prenatal care (PNC) utilization behaviors associated with quitting e-cigarette and dual use with conventional cigarettes remain understudied. Objective To examine the influence of socio-demographic characteristics and PNC utilization in the cessation of cigarette, e-cigarette, and dual-use during pregnancy, using Pregnancy Risk Assessment Monitoring System (2016–2022) data. Methods We analyzed data from 223,793 respondents (weighted count = 11,475,844) with singleton births who reported cigarette and/or e-cigarette use during the three months before and the last three months of pregnancy. Socio-demographic and PNC cessation correlates for cigarette, e-cigarette, and dual-use were examined versus continuation using logistic regression analysis. The Adequacy of Prenatal Care Utilization (APNCU) Index assessed PNC. Associations were expressed as adjusted odds ratios with 95% confidence intervals [AOR (95%CIs)]. Results Tobacco product use declined from 16.9% pre-pregnancy to 7.5% by late pregnancy. Pregnancy-associated cessation rates were 53.7% for cigarettes, 81.0% for e-cigarettes, and 48.1% for dual-use. Primiparity was associated with higher odds of quitting across all groups: cigarettes [1.8 (1.6‒2.0)], e-cigarettes [1.6 (1.2‒2.1)], and dual-use [2.3 (95% CI: 1.7‒3.1)]. Black race and Hispanic ethnicity were positively associated with cessation of cigarettes and dual-use, while Black race was also associated with higher odds of EC cessation. A higher smoking frequency was associated with reduced cessation odds of cigarette [0.2 (0.2‒0.3)] and dual-use [0.3 (0.2‒0.4)], while a higher vaping frequency was associated with reduced e-cigarette cessation [0.3 (0.2‒0.5)]. Inadequate APNCU Index was associated with lower odds of quitting cigarettes [0.6 (0.5‒0.7)] and dual-use [0.6 (0.4‒0.9)], but showed no significant association with e-cigarette cessation [0.9 (0.6‒1.5)]. Conclusions Distinct socio-demographic and PNC factors influence cessation patterns by product type. Findings underscore potential opportunities to integrate PNC with targeted cessation support, particularly for high-risk groups amid rising e-cigarette and dual use during pregnancy.